FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN PEMBERIAN OPINI DENGAN SKEPTISISME PROFESIONAL AUDITOR SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Pemeriksa BPK RI Perwakilan Provinsi Jawa Tengah) - Muhibul Hafidin, 11.05.52.0029; Badjuri, Achmad (Students Journal of Accounting and Banking, 2015)
This study aims to analyze the influence of ethics, experience, expertise and independence of the accuracy of giving opinions and influence of ethics, experience, expertise and independence of the accuracy of giving opinions through the auditors professional skepticism on BPK Representatives of the Province of Central Java. The population in this study were all inspectors who have had the Functional Audit certificate (JFP) and have experience as an examiner in the BPK at least 3 years. Sampling was done by using purposive sampling method and sample size were 99 respondents. Primary data collection method used was a questionnaire method. Data were analyzed using multiple linear regression model. The results showed that the ethics, expertise, and independence significant positive effect on the accuracy of giving opinions, whereas experience significant negative effect on the accuracy of giving opinions. Ethics, expertise and independence of the significant positive effect on the accuracy of the provision of the auditors opinion through professional skepticism, but experience significant positive effect on the precision of the provision of the auditors opinion through professional skepticism.Keywords: Ethics, Experience, Expertise, Independence, Professional Skepticism Auditors, The Appropriateness of Giving Opinions